Recent developments in Liquid Phase Electroepitaxial growth of bulk crystals under magnetic field - Dost, Sadik; Lent, Brian; Sheibani, Hamdi; Liu, Yongcai (Comptes rendus. Mecanique, 2004)
This review article presents recent developments in Liquid Phase Electroepitaxial (LPEE) growth of bulk single crystals of alloy semiconductors under an applied static magnetic field. The growth rate in LPEE is proportional to the applied electric current. However, at higher electric current levels the growth becomes unstable due to the strong convection occurring in the liquid zone. In order to address this problem, a significant body of research has been performed in recent years to suppress and control the natural convection for the purpose of prolonging the growth process to grow larger crystals. LPEE growth experiments show that the growth rate under an applied static magnetic field is also proportional and increases with the field intensity level. The modeling of LPEE growth under magnetic field was also the subject of interest. Two-dimensional mathematical models developed for the LPEE growth process predicted that the natural convection in the liquid zone would be suppressed almost completely with increasing the magnetic field level. However, experiments and also three-dimensional models have shown that there is an optimum magnetic field level below which the growth process is stable and the convection in the liquid zone is suppressed, but above such a field level the convective flow becomes very strong and leads to unstable growth with unstable interfaces. To cite this article: S. Dost et al., C. R. Mecanique 332 (2004). Cet article présente une revue des développements récents en cristallogénèse par Electro-Epitaxie en Phase Liquide (LPEE), des monocristaux d'alliages semi-conducteurs, sous l'effet d'un champ magnétique statique. La vitesse de croissance est proportionnelle à l'intensité du courant électrique. Néanmoins, pour des courants élevés, la croissance devient instable, à cause de la convection forte dans la zone liquide. Il y a eu beaucoup de recherches ces dernières années pour diminuer et maı̂triser la convection naturelle et faire croı̂tre des cristaux plus grands. Les expériences de croissance par LPEE montrent que la vitesse de croissance sous champ magnétique est proportionnelle, à l'intensité du champ magnétique. La simulation numérique de la croissance par LPEE en présence d'un champ magnétique, fut également, un important objet de recherche. Les simulations numériques, en deux dimensions, prévoient que la convection naturelle est quasiment supprimée lorsque l'intensité du champ magnétique s'accroı̂t fortement. Or, des expériences et simulations tri-dimensionnelles montrent l'existence d'une valeur de l'intensité magnétique au-dessous de laquelle la croissance est stable et la convection est supprimée ; mais, à des intensités plus élevées, l'influence de la convection est très forte, ce qui conduit à une croissance irrégulière et des interfaces instables. Pour citer cet article : S. Dost et al., C. R. Mecanique 332 (2004).